An Efficient Combinatorial Synthesis of Allocolchicine Analogues via a Triple Cascade Reaction and their Evaluation as Inhibitors of Insulin Aggregation. Issue 11 (5th September 2013) - Bhowmik, Subhendu; Khanna, Shruti; Srivastava, Kumkum; Hasanain, Mohammad; Sarkar, Jayanta; Verma, Sandeep; Batra, Sanjay
<x xml:space="preserve">Abstract</x> A controlled cascade: A divergent, diastereoselective and efficient one‐pot synthesis of allocolchicinoids via a cascade Suzuki–Michael addition–Carbocyclization sequence is described. The utility of the compounds as possible inhibitors of insulin aggregation is also presented.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>